2014
DOI: 10.1074/jbc.m113.506584
|View full text |Cite
|
Sign up to set email alerts
|

Role of Extracellular Signal-regulated Kinase 5 in Adipocyte Signaling

Abstract: Background: Regulation and function of ERK5 in adipose depots is not known. Results: Deletion of ERK5 in adipose depots increases adiposity and adipokine secretion. Reduced phosphorylation and potentiated NFATc4 nuclear localization are found. ERK5 also modulates PKA activation. Conclusion: ERK5 impinges on NFATc4 nucleo-cytoplasmic shuttling and modulates PKA activation in adipocytes. Significance: These results expand the repertoire of ERK5 physiological function and downstream targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 91 publications
(102 reference statements)
1
17
0
Order By: Relevance
“…In addition, the authors showed that CA-MEK5α overexpression could activate ERK5 by inhibiting its SUMOylation ( Shishido et al, 2008 ). Furthermore, in another study, blood glucose concentrations were found to be elevated in adipocyte specific ERK5 deficient mice and insulin sensitivity to be attenuated as compared with wild-type mice ( Zhu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the authors showed that CA-MEK5α overexpression could activate ERK5 by inhibiting its SUMOylation ( Shishido et al, 2008 ). Furthermore, in another study, blood glucose concentrations were found to be elevated in adipocyte specific ERK5 deficient mice and insulin sensitivity to be attenuated as compared with wild-type mice ( Zhu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we reported diabetic stimuli reduced the ERK5 transcriptional activity through ERK5-SUMOylation in endothelial cells, and that ERK5-SUMOylation was increased in a mouse model of STZ-induced diabetic cardiac dysfunction induced by myocyte apoptosis ( Le et al, 2012 ; Woo et al, 2008 ). Recently, it was reported that high fat diet Adipo-ERK5 deficient mice exhibited increased body weight as compared with control littermates, thus suggesting ERK5 plays a protective role of ERK5 in metabolic disease ( Shishido et al, 2008 ; Zhu et al, 2014 ). However, the role played by ERK5 in the diabetic pancreas has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that these signaling pathways are related to adipocyte differentiation and fat metabolism. MAPK signaling pathway involves four pathways, including ERK1/2, JNK, p38 MAPK and ERK5/BMK1, which have played an important role in adipopexis [52][53][54][55]. The Wnt signaling pathway is involved in the fate determination of the fat cell, adipogenic differentiation and lipometabolism [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…ERK5 has an opposing action to calcineurin on NFATc4-mediated gene transcription which changes the levels of adipokines expression. The deletion of ERK5 increased adiposity with dysregulation in adipokines secretion, leptin resistance, and impaired glucose handling [116]. It has been identified that above effect of ERK5 in diabetic nephropathy is mediated by TGFβ1 induced phosphorylation of MEK5 without involvement of the MAP3K Ras [117].…”
Section: Role Of Erks In Glucose Metabolism and Insulin Resistancementioning
confidence: 99%